La motricidad fina y las técnicas grafoplásticas en los niños del inicial II de la escuela de educación básica “Azogues” del cantón Espíndola, periodo 2018 - Santorun Cumbicus, Mariuxi Jazmin (2018)
The present research work denominate: Fine Motor and Graphoplastic Techniques in the children of initial II school of Basic Education "Azogues" of Espíndola canton, Period 2018, has as purpose to contribute and support the fine motor development process in children from four to five years old, for this reason, the general objective was to: Contribute to the strengthening of fine motor skills through the graphoplasts techniques in the children of the initial II of the Basic Education School "Azogues" of the Espíndola canton. It is a scientific-social research of a descriptive nature with quantitative-qualitative approach. The methods used are: Scientific, qualitative and analytical-synthetic, the information was collected through instruments and techniques such as: Interview with the teacher, observation guide for fine motor skills applied to the 7 children of the initial II same that were elaborated by the researcher and a table of fine motor skills of the authors (Carrillo & Valladolid) adapted by the author of the present investigation. Results that allowed us to conclude that: The difficulties of fine motor skills in the children of the initial II, are evidenced in the inadequate motive power, lack of coordination in the movements, need for sure and perfect grip, therefore it is recommended: That the director direct the Methodological preparation and training of teachers in the use of graphoplastic techniques to promote an adequate development in the fine motor skills of the children of the initial II, based on curricular activities associated with games appropriate to the rhythm of the children and that motivate them for a developer learning